Adjusting expectations or maintaining first impressions? The stability of teachers' expectations of students' mathematics achievement. (October 2021) - Timmermans, Anneke C.; Rubie-Davies, Christine M.; Wang, Shengnan
Abstract: The issue of teacher expectation stability is crucial in understanding the self-fulfilling prophecies generated by teacher expectations. However, currently there is a lack of empirical evidence related to teacher expectation stability. The aim of the current study was to assess the temporal stability of teacher expectations of their students' mathematics achievement within the timeframe of one school year. Random-Intercept Cross-Lagged Panel Models were employed based on a sample of 2536 students taught by 89 teachers in New Zealand elementary and middle public schools. Strong rank order stability was found in teacher expectations at the between-student level. Expectation instability was present at the within-student level. Paths from student mathematics achievement to teacher expectations were stronger than the paths in the opposite direction, indicating that teachers adapted their expectations for students to fall in line with student performance and continued to do so throughout the year. Highlights: Teachers' rank ordering of students remained stable over three time periods (77). Across one year, teachers' expectations for individual students were not stable (82). Teachers adapted their expectations throughout the year to reflect achievement (80). Paths from student achievement to teacher expectations were directionally dominant (85).